2004
DOI: 10.1002/ana.20178
|View full text |Cite
|
Sign up to set email alerts
|

Novel haplotypes in 17q21 are associated with progressive supranuclear palsy

Abstract: Progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) are sporadic neurodegenerative diseases presenting as atypical parkinsonian disorders, characterized by the presence of tau-positive neurofibrillary tangles. Recently, an extended haplotype (H1E) of 787.6 kb that comprises several genes including MAPT showed increased association with PSP. The objective of this study was to determine the size of the H1E haplotype associated with PSP and CBD in different populations and to identify specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…[13][14][15][16] Recent studies have reported that whereas the H2 haplotype is in fact a single nonrecombining haplotype, the more common H1 haplotype is more diverse, showing typical linkage disequilibrium (LD), although not with H2. 12,[17][18][19] This diversity can be tagged through five single-nucleotide polymorphisms (SNPs) and the aforementioned delIn9. 13,16 The H1c variant of this haplotype is reported to be the predominant cause of the H1 association with progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) 17,20,21 and more recently has been associated with AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Recent studies have reported that whereas the H2 haplotype is in fact a single nonrecombining haplotype, the more common H1 haplotype is more diverse, showing typical linkage disequilibrium (LD), although not with H2. 12,[17][18][19] This diversity can be tagged through five single-nucleotide polymorphisms (SNPs) and the aforementioned delIn9. 13,16 The H1c variant of this haplotype is reported to be the predominant cause of the H1 association with progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) 17,20,21 and more recently has been associated with AD.…”
Section: Introductionmentioning
confidence: 99%
“…12,[17][18][19] This diversity can be tagged through five single-nucleotide polymorphisms (SNPs) and the aforementioned delIn9. 13,16 The H1c variant of this haplotype is reported to be the predominant cause of the H1 association with progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) 17,20,21 and more recently has been associated with AD. 16 Prior studies of MAPT associations with AD had produced inconclusive findings; 14,15,[22][23][24][25] however, the study of Myers et al 16 was the first study to assess the impact of this H1 diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent haplotype H1 was reported to regulate transcription of MAPT and associated with tauopathies [6,9] . Further studies have shown that a subhaplotype of H1 (H1c) is largely responsible for the association between the haplotype H1 and the sporadic tauopathies [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several polymorphic sites, which tag the diversity between the H1 and the H2 haplotypes, segregate together, or in genetic terms are in linkage disequilibrium (LD). Several studies have consistently shown that the H1 haplotype (the more common in humans) is strongly associated, whereas the H2 haplotype is underrepresented in PSP patients [7,8], suggesting that H1 predisposes to or that H2 protects from PSP, or both.…”
mentioning
confidence: 97%